A Main Class of Integral Inequalities with Applications - Masjed-Jamei, Mohammad; Omey, Edward; Dragomir, Sever S. (Mathematical Modelling and Analysis, 2016)
In this paper, we define some integral transforms and obtain suitable bounds for them in order to introduce a main class of integral inequalities including Ostrowski and Ostrowski-Gr¨uss inequalities and various kinds of new integral inequalities. In this sense, we also introduce a three point quadrature formula and obtain its error bounds.